Recommendations for Occupational Safety and Health (K3) as a Means in Increasing Employee Performance Productivity - Muhammad Rifqi; Fajarianto, Otto; Husni Thamrin (IJESS International Journal of Education and Social Science, 2023)
Occupational Health and Safety (K3) is an important aspect in an industrial environment that aims to protect employees from various risks and hazards that may occur during the production process. This study aims to analyze the role of OSH in increasing productivity and quality of work in various industrial sectors. Regulation of the Minister of Manpower No. 4 of 1987 confirms that every agency that employs employees with a number of over 100 people or more is obliged to pay attention to the occupational safety and health of its employees, but unfortunately Not all agencies apply K3 to these agencies. Working with a healthy, safe and comfortable body and environment is what all workers want. The physical environment of the workplace and organizational environment are very important in influencing the social, mental and physical life of workers. The health of a workplace environment can have a positive influence on worker health, such as increasing worker morale, reducing absenteeism and increasing productivity. On the other hand, an unhealthy or unhealthy workplace (often exposed to hazardous substances/items affecting health/occupational safety) can increase the number of unhealthy and even accidents, lower the quality of workers' health, increase health costs and many other negative impacts. This study uses a qualitative approach by collecting data from various sources, including literature studies and interviews with industry practitioners who are experienced in OSH implementation. The results showed that OSH has a significant role in increasing employee productivity by reducing absenteeism due to work-related accidents and diseases. In addition, the implementation of an effective OSH program can reduce the number of work accidents and potential injuries, which ultimately improves work quality and operational efficiency. This study concludes that OSH is not only the responsibility of the company, but also the community and government must be involved in ensuring a safe and healthy work environment. With the implementation of OSH management, it is hoped that healthy workers will make productive workers, which is very important for the success of company and agency businesses and national development.